(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The Algae Culture Collection of Kyiv University (ACKU) is a non-profit subdivision of Department of Botany that is located at the National Taras Shevchenko University,f Kyiv, which not only maintains an important resource of algal biodiversity but affords all its algal strains for study by scientific community for scientific and educational purposes. The ACKU comprises a great number of freshwater species. At the moment ACKU holds 540 strains that belong to 109 genera and 283 species (including 246 authentic strains), mostly from Chlorophyta and Xanthophyta.